Formungstendenzen und Formungsphasen in der Entwicklung der ländlichen Kulturlandschaft seit dem hohen Mittelalter, besonders in Nordwestdeutschland - Fliedner, Dietrich (ERDKUNDE, 1969)
The artcile deals with the problem of temporal divisions in the development of the cultural landscape since high medieval times. Following on from studies made by H. Overbeck and H. Jäger, an attempt is made, with the help of various criteria, to reveal the most important pattern-forming tendencies and to temporally demarcate them. The basis of the division lies in an attempt to serialise different types of form, in the various difficulties involved in the process and with the spatial organisation of the cultural landscape. The periods of high medieval agricultural expansion (and, after the retreat phenomena of the late middle ages, the expansion of modern times) can each be divided into three phases (in which the dates should be interpreted as mean values): 1000-1070: small-scale land clearance, non-uniform settlement types. 1070-1230: large-scale land clearance under the influence of territorial rulers, uniform settlement types. 1230-1350: large-scale land clearance, strong urban influence on the form of the cultural landscape. 1350-1450/1500: late medieval retreat periods, pronounced social and economic changes. 1450/1500-1700: small-scale land clearance, non-niform settlement types. 1700-1850: large-scale land clearance under the influence of the State, uniform settlement types. 1850-1950: expansion and improvement of existing settlements, stronger urban influence. 1950-till today: increasing fallow phenomena and decrease in farm numbers, strong social and economic restructuring. The phased changes in pattern-forming tendencies reflect, during the settlement expansion periods, the building up of a sectoral and spatial social and economic order, while a caesura occurred with the retreat phenomena.